Impact of forced displacement on synergetic identity in selected works of Lakshmi Persaud and Caryl Phillips - Wagaa, Intisar Mohammed (2019)
This research studied Lakshmi Persaud’s For the Love of My Name (2000) and Sastra (1993); and Caryl Phillips’s Crossing the River (1993), and The Nature of Blood (1997) from a postcolonial perspective. Therefore, the research applied Homi Bhabha’s concept of displacement to examine the reasons of forced movement in the selected works which has been rarely applied. It also applied the concept of synergy to explore the effect synergetic identity in the selected novels. The concept of synergy was hardly applied to analyze the changing identity depicted in the selected works. The synergetic identity was argued as the preceding identity change that paves the way for the characters’ hybrid identity. As such, the research is significant in the sense that it examined the transformation of the African and Caribbean identity through two phases. The first phase is the African and Caribbean native identity which is forced to leave homeland through displacement experience. The second phase is the synergetic identity which forces the displaced people to adopt the host lands’ culture and tradition. Accordingly, their native identity undergoes a radical change. Consequently, the relationship between the native people and the host land’s people was explored in the light of Edward Said’s concept of self-other relationship, which was scarcely applied to analyze the selected novels. In this sense, the synergetic identity was limited to the analysis of the characters’ initial influence by the host land’s culture and traditions. Robert Young’s concept of synergy was applied to reveal the host land’s basic influence upon the displaced people’s identity. Then, they gradually amalgamate with the host land’s people. By time, the displaced people’s identity becomes hybrid; i.e., consisting of two discrepant culture, the homeland’s culture and the host land’s culture. Additionally, utilizing the concept of hybridity is scarcely used to analyze the novels’ embodiment of colonial synergy and displacement. Consequently, this research argued that both Persaud and Phillip indirectly critique the oppressed and displaced people in order to elevate their socio-cultural status in the world.